2017
DOI: 10.3390/su9091611
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Electricity Generation from Wind Corridors of Pakistan (Two Provinces): A Technical Proposal for Remote Zones

Abstract: Abstract:The non-renewable energy resources are limited and depleting gradually. As such, energy security has attained the greatest amount of attention globally than ever before. In the meantime, energy crises are already affecting the developing countries such as Pakistan, even though one-third of the population of the country is not even not connected to the national electricity grid. The population with access to on-grid electricity is enduring load shedding of more than 12 h a day. This situation is alarmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Mazhar Hussain et al [20] have presented a technical proposal for off-grid electricity generation from six wind sites of two provinces in Pakistan. In the meantime, Yousaf Ali et al [32] have only identified six key criteria (i.e., wind speed, wind power density, capacity factor, transport cost, distance from grid station, and population density) for wind project site selection, but have not implemented these criteria.…”
Section: Factor Analysis (Fa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mazhar Hussain et al [20] have presented a technical proposal for off-grid electricity generation from six wind sites of two provinces in Pakistan. In the meantime, Yousaf Ali et al [32] have only identified six key criteria (i.e., wind speed, wind power density, capacity factor, transport cost, distance from grid station, and population density) for wind project site selection, but have not implemented these criteria.…”
Section: Factor Analysis (Fa)mentioning
confidence: 99%
“…Table 3. International wind power classification at 10 m, 30 m, and 50 m heights [20]. As per these international standards, the following two factors are essentially vital and should be considered well before choosing or selecting a site for wind tower installation [21]: (a) The selected region must be windy and cover all of the parts of the region as per relevant wind power classification.…”
Section: Meteorological Data Of the Selected Locationsmentioning
confidence: 99%
“…This also changed the energy consumption paradigm across various sectors in the economy (Figure 2), adversely impacting some of these sectors such as transportation and power generation sectors [9,10]. has limited fossil energy resources of its own and has a low per capita energy consumption of 501.6 kg oil equivalent compared to the global average of 1790 kg oil equivalent [7,8]. Pakistan is, therefore, facing significant challenges in the energy sector towards meeting the demand which is growing at a rate of 11 to 13% per year.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these power policies, the oil import bill, which was USD 530 million in 1994, has surpassed USD 1400 million in recent years. This expenditure on importing oil represents 40% of the has limited fossil energy resources of its own and has a low per capita energy consumption of 501.6 kg oil equivalent compared to the global average of 1790 kg oil equivalent [7,8]. Pakistan is, therefore, facing significant challenges in the energy sector towards meeting the demand which is growing at a rate of 11 to 13% per year.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, the developed areas were with limited supply of gas infrastructure. As the population growth has shown steep increase, the demand for electricity is also increased and electricity supply crisis and power planning and policies have been address by various authors Valasai et al 2017;Baloch et al 2017). More recently, it has been reported that a supply and demand gap of the gas has increased due to electricity supply to nation, for power generations.…”
Section: Pakistan' Natural Gas Demandmentioning
confidence: 99%